Analysis of adhesive and biofilm-forming properties of field isolates of microor-ganisms for pig houses under the action of disinfectants “Sviteco PIP Multi” and “Vulkan Max” - V. O. Myronchuk; R. A. Peleno (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Adhesion is a critically important condition for the development of microbes. It allows them to attach to the surfaces of certain objects and obtain nutrients for survival, reproduction, and subsequently, the formation of biofilms in which microorganisms, compared to planktonic forms, demonstrate increased resistance to antimicrobial agents, including disinfectants. The work aimed to investigate the effect of disinfectants “Sviteco PIP Multi” and “Vulcan Max” on the adhesive and biofilm-forming ability of field isolates of microorganisms from pig housing. It was found that before the action of disinfectants on the studied isolates, the average adhesion index varied from 1.4 to 5.8 microbes per erythrocyte (MO/RBC), the erythrocyte participation coefficient was from 42 to 98 %, the adhesion index was from 2.5 to 5.92, all of them had biofilm-forming ability and formed biofilms of high and medium density. Under the action of disinfectants, a significant decrease in the adhesive ability of microorganisms was noted. When interacting with Vulcan Max, the maximum SPA index of isolates did not exceed 1.9 MO/RBC, which indicates a decrease in their level of adhesiveness to a low level. The agent “Sviteco PIP Multi” demonstrated an even more pronounced effect, reducing the value of the indicated indicator for all isolates, except E. coli, B. subtilis, and B. megaterium, to a minimum level. In the last two cases, an increase in the average adhesion index from low to medium was noted. Similar changes were also found in the study of the erythrocyte participation coefficient. Before interaction with disinfectants, its value ranged from 63 to 98 %. Under the influence of Vulcan Max, this indicator decreased almost 2 times and ranged from 39 to 54 %. The agent “Sviteco PIP Multi” caused a decrease in this indicator by almost 2.2 times in all studied isolates, except for B. subtilis and B. megaterium, where its increase was noted by 1.5 times. According to the adhesiveness index, C. jejuni, S. salivarius, B. subtilis, B. megaterium, C. perfringens, P. mirabilis, and C. freundii were classified as medium, and E. faecium, E. faecalis, S. aureus, P. aeruginosa, K. pneumoniae and E. coli were classified as highly adhesive. Under the action of the “Vulcan Max” agent, the adhesion index of all highly adhesive isolates and C. jejuni, S. salivarius, B. subtilis, and B. megaterium decreased to an average level in C. perfringens – to a low level, and in P. mirabilis and C. freundii – remained unchanged. After the interaction of the “Sviteco PIP Multi” agent with the studied isolates, the adhesion index of highly adhesive E. faecalis, S. aureus, P. aeruginosa, and E. coli, and the moderately adhesive P. mirabilis and C. freundii corresponded to the indicators of low-adhesive ones, E. faecium and K. pneumoniae and C. jejuni, S. salivarius and C. perfringens – were non-adhesive, and B. subtilis and B. megaterium from moderately adhesive ones became highly adhesive, since their index increased by 1.8 and 1.7 times. All the studied isolates could form biofilms. Under the influence of disinfectants, there was a decrease in biofilm-forming activity, which was more pronounced under the action of Sviteco PIP Multi, as evidenced by a decrease in the density of the formed microbial biofilms, with the further exception of B. subtilis and B. megaterium, which after interacting with it formed denser biofilms.